2023
DOI: 10.1155/2023/1554599
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of a CT Radiomics-Based Nomogram for the Overall Survival of Patients with Nonmetastatic BCLC Stage C Hepatocellular Carcinoma after Stereotactic Body Radiotherapy

Abstract: Purpose. This study aimed to investigatie the feasibility of pretherapeutic CT radiomics-based nomograms to predict the overall survival (OS) of patients with nondistant metastatic Barcelona Clinic Liver Cancer stage C (BCLC-C) hepatocellular carcinoma (HCC) undergoing stereotactic body radiotherapy (SBRT). Methods. A retrospective review of 137 patients with nondistant metastatic BCLC-C HCC who underwent SBRT was made. Radiomics features distilled from pretherapeutic CT images were selected by the method of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…The results showed that the integrated model combining the RS and clinical factors could more effectively predict RFS after the LR of BCLC stage 0 to B stage HCC patients and could effectively stratify patients according to prognostic risk. Wang et al 12 investigated the feasibility of pretherapeutic CT radiomics-based nomograms for predicting the overall survival of patients with nondistant metastatic BCLC stage C HCC who underwent stereotactic body radiotherapy, and the resulting model has great potential. Both studies above demonstrate that CT radiomics can be used to predict the therapeutic effect and prognosis of HCC patients in different BCLC stages with different treatment modalities.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the integrated model combining the RS and clinical factors could more effectively predict RFS after the LR of BCLC stage 0 to B stage HCC patients and could effectively stratify patients according to prognostic risk. Wang et al 12 investigated the feasibility of pretherapeutic CT radiomics-based nomograms for predicting the overall survival of patients with nondistant metastatic BCLC stage C HCC who underwent stereotactic body radiotherapy, and the resulting model has great potential. Both studies above demonstrate that CT radiomics can be used to predict the therapeutic effect and prognosis of HCC patients in different BCLC stages with different treatment modalities.…”
Section: Discussionmentioning
confidence: 99%
“…The AIC serves as a standard for assessing the quality of fit of statistical models. It is built upon the principle of entropy and establishes a benchmark for evaluating the complexity of the estimated model and the accuracy of the fitted data [32,33]. When selecting the optimal model from a given set of models, typically, the model with the lowest AIC is chosen.…”
Section: Factor Analysis and Model Constructionmentioning
confidence: 99%